1986
DOI: 10.1159/000146234
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Brainstem Connections of the Rat Supratrigeminal Region

Abstract: Efferent and afferent connections of the supratrigeminal region were studied in the rat using iontopho-retically delivered horseradish peroxidase and Phaseolus vulgaris leuco-agglutinin. Projections of supratrigeminal efferents were found to the contralateral supratrigeminal region, to the ipsi- and contralateral trigeminal motor nuclei and the medullary reticular formation, and to the ipsilateral facial and hypoglossal motor nuclei. Neurons projecting to the supratrigeminal region were located in the contrala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Although we have a reasonably good understanding of the neuronal circuits responsible for a number of oralmotor reflexes (see Lund, 1991;Nakamura and Katakura, 1995), the precise identity of the constituent neurons of the central circuits, known as central pattern generators (CPGs), underlying oral-motor rhythmic movements such as suckling and mastication remain elusive. Nevertheless, progress has been made in defining (1) the minimal regions of the brain stem compatible with oral-motor rhythmic activity (Chandler and Tal, 1986;Tanaka et al, 1999), (2) synaptic interconnections between trigeminal interneuronal nuclei in those regions (Mizuno, 1970;Rokx et al, 1986;Bourque and Kolta, 2001), and (3) intrinsic membrane properties and discharge characteristics of neurons in those regions (Inoue et al, 1992Bourque and Kolta, 2001;Min et al, 2003;among others). In the present study we found that a small population of SupV neurons exhibit conditional burst-generating properties that are most associated with multipolar neurons that discharge in either tonic or delayed-firing mode.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have a reasonably good understanding of the neuronal circuits responsible for a number of oralmotor reflexes (see Lund, 1991;Nakamura and Katakura, 1995), the precise identity of the constituent neurons of the central circuits, known as central pattern generators (CPGs), underlying oral-motor rhythmic movements such as suckling and mastication remain elusive. Nevertheless, progress has been made in defining (1) the minimal regions of the brain stem compatible with oral-motor rhythmic activity (Chandler and Tal, 1986;Tanaka et al, 1999), (2) synaptic interconnections between trigeminal interneuronal nuclei in those regions (Mizuno, 1970;Rokx et al, 1986;Bourque and Kolta, 2001), and (3) intrinsic membrane properties and discharge characteristics of neurons in those regions (Inoue et al, 1992Bourque and Kolta, 2001;Min et al, 2003;among others). In the present study we found that a small population of SupV neurons exhibit conditional burst-generating properties that are most associated with multipolar neurons that discharge in either tonic or delayed-firing mode.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this finding, Grofova and Keane (1991) reported a sparse, yet consistent, projection from the PPTg to the lateral facial motor neurons by using anterograde tract tracing. Combined with our present data, these findings clearly demonstrate that the PPTg is an important source of input to wFMNs.Sparse to moderate anterograde and retrograde labeling was also observed bilaterally in the pontine reticular nucleus, in the subpeduncular tegmental nucleus, and in the subcoeruleus Rokx et al (1986) demonstrated that the supratrigeminal nucleus projects to intermediate and dorsal regions of the facial nucleus and only rarely to the lateral facial nucleus. Thus, the scarcity of retrograde labeling in the supratrigeminal nucleus in our study indicates that our injections were indeed confined to the lateral subdivision of the facial nucleus.…”
mentioning
confidence: 88%
“…Components of the motor trigeminal complex, including the motor trigeminal and supratrigeminal nuclei, contained no, or only sparse, labeled neurons and terminals. Significantly, an anterograde tract-tracing study by Rokx et al (1986) demonstrated that the supratrigeminal nucleus projects to intermediate and dorsal regions of the facial nucleus and only rarely to the lateral facial nucleus. Thus, the scarcity of retrograde labeling in the supratrigeminal nucleus in our study indicates that our injections were indeed confined to the lateral subdivision of the facial nucleus.…”
Section: Labeling In the Metencephalonmentioning
confidence: 99%
“…The RF surrounding 5N projects bilaterally to 5N and includes cells in the supratrigeminal nucleus (Su5) located dorsal to 5N, the intertrigeminal nucleus (I5) interposed between 5N and the principal trigeminal sensory nucleus, and the juxtatrigeminal area (Jx5) ventral to 5N (Travers and Norgren, 1983;Vornov and Sutin, 1983;Rokx et al, 1986;Appenteng et al, 1990;Yoshida et al, 2009). More recently, the region just medial to the ventromedial subdivision of 5N (MPe5) has been identified as having a close association with adjacent jaw-opener motoneurons (McDavid et al, 2006;Yoshida et al, 2009).…”
Section: Pontine Projectionsmentioning
confidence: 99%